British insurance - Clayton, George (London: Elek Books Ltd., 1971)
This study has been split into four parts. Part 1 explains the formative period: before 1800. Part two- the period of ascendency 1800-1914. Part three- the period of challenge 1914-1971; and Part four- the contemporary industry.
Includes bibliographical references: p. 373-376.
ne 4/05/2018
Loans
Keywords: Insurance; Insurance - British